Improvement of the Production Process for Handwoven Shawls with Nature Dye Printing to Add Value and Reduce Waste by Applying Value Strem Mapping - Wichachai, Natnicha; Suphon, Thanyakan; Jomthrak, Sirinart; Saengsathien, Arjaree; To-on, Piyanat (Journal of Engineering and Industrial Technology, Kalasin University, 2024)
This research focuses on studying the production process of handwoven shawls with natural dye printing (ECO PRINT) with the objectives of analyzing production steps and developing strategies to reduce waste and enhance product value. The research involved field data collection at Ban Dong Noi, Moo 5, Huai Pho Subdistrict, Mueang District, Kalasin Province, using production process charts and value stream mapping as key analytical tools. The production process is divided into two main parts: cotton weaving, consisting of seven steps with an average duration of 761 minutes per cycle, and natural dye printing, comprising 24 steps with an average duration of 405.6 minutes per cycle. Data collection and time analysis were conducted over five production cycles. The analysis identified key wastes in the process, including unnecessary movements and waiting times, which can be addressed by workspace organization, the use of supporting technologies such as storage tools and automation, and improved time management. These improvements reduced production time by 5.2% and movement distances by 40%, enhancing process efficiency, minimizing waste, and sustainably increasing the value of ECO PRINT products.